Resolusi Konflik Sosial melalui Pendekatan Komunikasi di Lingkungan Monjok dan Karang Taliwang Kota Mataram - Siti Nurul Yaqinah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
The conflict is one of the phenomena that occurs as part of the dynamics of thecommunity. Among the social conflict that rooted strongly in the community of the city ofMataram was the conflict Monjok and Karang Taliwang. Therefore, this research aims toknow the background of the occurrence of social conflict, the impact of conflict on thelives of communities and communications in an effort to approach conflict resolution inan environment of Monjok and Karang Taliwang. This research uses a qualitativedescriptive method, data obtained through interviews, observation and documentation.The analysis used was the reduction of the data, the presentation of data, and thewithdrawal of the conclusion. To test the validity of the data, the researchers conductingthe study, extra time triangulation of methods and sources, and the associatedexamination. The results obtained in this study are a conflict that occurs between thecitizens of Monjok and Karang Taliwang triggered by the removal of the trash containerby Karang Taliwang minimal coordination and dissemination so as to trigger the action of the destruction caused by the citizens Monjok. Another trigger is a young man's disputeand the existence of a third party that provokes the situation for transferability. So, theimpact on the conflict; psychological society, communication, economic impact andstalled social impact. Therefore, some approaches used in handling the conflict approachis communication through Consolas, the communication approach through negotiationsor deliberations, approach to communication through mediation and communicationapproaches involving stakeholders.